2018
DOI: 10.1002/eji.201847707
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐shed antigen CA125 blocks complement‐mediated killing via suppression of C1q‐antibody binding

Abstract: C1q-engagement with IgG and IgM type antibodies is the initiating step of classical complement-mediated immunity. The tumor shed antigen CA125 has been reported to have immunosuppressive effects on host tumor responses as well as commercially approved and experimental monoclonal antibody (mAb)-based therapeutic agents. To better understand this effect, molecular and cellular studies were carried out testing the ability of CA125 to perturb the classical complement pathway. Here, we show that patient-derived CA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…CA125 also inhibited the RTX-dependent activation of the Fc-gamma receptor FCGR3A/CD16a (‘Fc receptor’; Fig. 1B ), confirming the mechanism of action previously reported for the reduced ADCC activity of farletuzumab, whereby the binding of CA125 to this antibody reduces its engagement with both Fc receptor as well as C1q ( 13 , 15 , 19 ). Furthermore, CA125 did not decrease RTX binding to CD20, thus ruling out reduced binding to the target cells as a mechanism of decreased ADCC and CDC ( Fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…CA125 also inhibited the RTX-dependent activation of the Fc-gamma receptor FCGR3A/CD16a (‘Fc receptor’; Fig. 1B ), confirming the mechanism of action previously reported for the reduced ADCC activity of farletuzumab, whereby the binding of CA125 to this antibody reduces its engagement with both Fc receptor as well as C1q ( 13 , 15 , 19 ). Furthermore, CA125 did not decrease RTX binding to CD20, thus ruling out reduced binding to the target cells as a mechanism of decreased ADCC and CDC ( Fig.…”
Section: Resultssupporting
confidence: 87%
“…3C ), RTX N109D showed CD20-specific binding and affinity comparable to parent RTX. Since CA125 inhibits C1q binding to RTX, leading to reduced CDC activity ( 19 ), we investigated whether this CA125 effect was attenuated when using RTX N109D. Our previous analysis already indicated that C1q binding to RTX N109D was in fact less suppressed by CA125 compared with RTX ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations